Digital Isnād System and Religious Legitimacy: Examining The Qualification and Authorization Process of Islamic Authority on Cariustadz.ID Platform - Alwi Bani Rakhman; Lukman Zain; Anisatun Muthi'ah (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2025)
This study examines how digital platforms reconfigure the classical Islamic isnād system, contributing to discourse on religious authority transformation in the digital age. The isnād—traditionally a linear teacher-student chain establishing scholarly credibility—faces challenges in contemporary contexts where physical proximity no longer governs religious instruction. Employing qualitative case study methodology, this research analyzes CariUstadz.id through interviews, document analysis, and platform observation. The findings reveal systematic isnād reconceptualization through two mechanisms. First, the platform's Expert Council (Majelis Dewan Pakar) conducts centralized vetting, functioning as a digital fatwa verification board performing rigorous credential assessment before endorsement. Second, transparent public display of validated credentials makes scholarly legitimacy immediately accessible. This dual mechanism preserves classical principles—transmission continuity (al-tasalsul) and scholarly credibility (maqbūliyyah)—while adapting them digitally: linear chains are replaced by centralized, technology-facilitated authentication maintaining epistemic rigor without physical co-presence. This reconfiguration significantly impacts contemporary Islamic practice. By institutionalizing verification previously embedded in personal relationships, the platform democratizes access to authenticated guidance while maintaining standards. Digital platforms thus serve as mediating institutions bridging classical knowledge transmission and technological realities, ensuring both accessibility and authenticity in an increasingly digitized religious landscape.